Effects of crude protein supplementation during beef cow’s mid-gestation on the offspring performance, physiology and metabolism - Nascimento, Karolina Batista (2021)
This work aimed to quantify the effects of protein supplementation during the mid-gestation of beef cows on the performance, metabolism, and physiology of the offspring. This study was divided into two repetitions and comprising 24 and 19 Tabapuã beef cows in each period, respectively. From 102 ± 5 to 208 ± 6 days of gestation, cows were distributed in a completely randomized design in a 2 × 2 factorial arrangements with the following treatments: two conditions of maternal nutritional management (MN) and offspring sex (OS). Control cows (CON; n = 24) were fed a basal diet with corn silage and sugarcane bagasse; while the supplemented group (SUP; n = 19) received 3.5 g/kg of body weight (BW) of a supplement with 40% crude protein (CP) per day. The offspring were evaluated from birth to 445 days of age in the following phases: cow-calf (0 – 210 days), background (255 – 320 days), growing 1 (321 – 381 days), and growing 2 (382 – 445 days) phases. Statistical differences were considered when P < 0.10. The SUP offspring was 3.8 kg; 16.4 kg and 30.8 kg heavier at birth, weaning, and at 445 days of age, respectively (P ≤ 0.049). SUP calves had greater morphometric measurements at birth and weaning. SUP calves had 26% greater muscle fiber area compared to CON animals at 30 days of age (P = 0.007). An MN × OS interaction for regulation of MyoD and FN1 genes (P ≤ 0.057) was verified in the Longissimus thoracis muscle of the offspring at 7 days. Maternal supplementation also increased mTOR expression (P = 0.056) at 7 days. At 445 days of age, the SUP offspring showed lower expression of the CPT2 gene (P = 0.037), while the ACACA and LPL genes were more expressed (P ≤ 0.090). SUP-females at 445 days of age showed higher expression of PPARG, FABP4, and SCD1 genes (P < 0.001). Maternal protein restriction exhibited sex-dependent responses on insulin (P = 0.076) and IGF-1 (P = 0.002) levels at weaning. However, these differences in hormone levels disappeared at 445 days of age (P > 0.10). The offspring from SUP dams consumed 11.3%; 9.2% and 7.9% of dry matter (DM) additional at weaning, growing 1 phase, and in the entire confinement period respectively (P ≤ 0.096). The feed efficiency for weight gain was not affected by the MN (P > 0.10). There was an MN × OS interaction on the OM (P = 0.070) digestibility at weaning; on DM and NDF (P ≤ 0.086) at background phase; and on DM, OM, CP, NDF, and TDN (P ≤ 0.089) at growing 2. Overall in the growing 2 phase, the nutrients digestibility was reduced in SUP-males. The ingestive behavior of the offspring was affected by maternal nutrition. In conclusion, prenatal protein supplementation improves the offspring's performance, favors intramuscular fat deposition, and increases the offspring's intake pattern, but reduces the nutrients digestibility of high-energy diets in males.